Strategi Komisi Penyiaran Indonesia Daerah (Kpid) Sumatera Barat Dalam Mengawasi Penyiaran Iklan Politik Pada Masa Pemilihan Umum Kepala Daerah (Pemilukada) 2024 - David Kurniawan (CV. ITTC INDONESIA, 2026)
This study investigates the approach used by the West Sumatra Regional Indonesian Broadcasting Commission (KPID) to monitor political advertisements broadcast during the 2024 regional elections. Monitoring political advertisements is crucial for maintaining a fair, transparent, and clean local democratic process. Representatives of broadcasting institutions, commissioners, secretariat staff, and staff who monitor broadcast content were interviewed and analyzed through observation and document analysis in this descriptive qualitative study. The results show that the West Sumatra KPID uses three main monitoring strategies: preventive, curative, and evaluative. The preventive strategy is used to disseminate regulations, issue technical guidelines, and coordinate across institutions. The curative strategy applies firm action against violations, such as warnings and broadcast suspensions. The evaluative strategy is used to produce reports and policy recommendations. In addition, the KPID is strengthening cooperation with the Elections Supervisory Agency (Bawaslu) and the public to increase oversight reach and provide a public complaints channel. However, oversight still faces numerous challenges. These include a lack of human resources and technology, a lack of technical regulations, and political pressure from local parties. Nevertheless, based on the media regulation theory used in this study, the West Sumatra KPID has attempted in various ways to balance freedom of expression with the public interest. They have done so in a flexible and involved manner. Going forward, this research is expected to help the KPID and related institutions improve their oversight of political advertising and broadcasting governance.